2016
DOI: 10.1002/jcb.25807
|View full text |Cite
|
Sign up to set email alerts
|

Basic Fibroblast Growth Factor Regulates REX1 Expression Via IL‐6 In Stem Cells Isolated From Human Exfoliated Deciduous Teeth

Abstract: Basic fibroblast growth factor (bFGF) regulates pluripotent marker expression and cellular differentiation in various cell types. However, the mechanism by which bFGF regulates REX1 expression in stem cells, isolated from human exfoliated deciduous teeth (SHEDs) remains unclear. The aim of the present study was to investigate the regulation of REX1 expression by bFGF in SHEDs. SHEDs were isolated and characterized. Their mRNA and protein expression levels were determined using real-time polymerase chain reacti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 37 publications
0
24
0
1
Order By: Relevance
“…Cells were isolated from the remaining dental pulp tissues of an extracted deciduous incisor from the proband and unaffected controls. Tissue explant technique was employed for cell isolation according to previous publications (Nowwarote, Pavasant, & Osathanon, ; Nowwarote, Sukarawan, Pavasant, & Osathanon, ). Cells were cultured in Dulbecco's Modified Eagle Medium (DMEM, Gibco ® ) containing 10% foetal bovine serum (FBS, Gibco ® , USA), 100 unit/ml penicillin, 100 μg/ml streptomycin, 5 μg/ml amphotericin B, 2 mM l‐glutamine (Glutamax ® ) at 37°C in 5%CO 2 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cells were isolated from the remaining dental pulp tissues of an extracted deciduous incisor from the proband and unaffected controls. Tissue explant technique was employed for cell isolation according to previous publications (Nowwarote, Pavasant, & Osathanon, ; Nowwarote, Sukarawan, Pavasant, & Osathanon, ). Cells were cultured in Dulbecco's Modified Eagle Medium (DMEM, Gibco ® ) containing 10% foetal bovine serum (FBS, Gibco ® , USA), 100 unit/ml penicillin, 100 μg/ml streptomycin, 5 μg/ml amphotericin B, 2 mM l‐glutamine (Glutamax ® ) at 37°C in 5%CO 2 .…”
Section: Methodsmentioning
confidence: 99%
“…Cells were maintained in growth medium supplemented with 50 μg/ml ascorbic acid, 10 mM beta‐glycerophosphate, and 100 nM dexamethasone. Mineral deposition was examined by alizarin red S staining according to previous publications (Nowwarote et al., , ). The expression of osteogenic marker genes was evaluated using quantitative polymerase chain reaction.…”
Section: Methodsmentioning
confidence: 99%
“…Several studies have reported that SHEDs can be induced into adipogenic lineage [6,[32][33][34]. After cultured in an adipogenic medium, SHEDs' morphology changed from spindle-like to polygonal shapes and lipid vacuoles were observed, along with the increased in PPARγ2 and LPL mRNA [32].…”
Section: Adipogenic Differentiation Potentialmentioning
confidence: 99%
“…Further, bFGF promotes colony-forming unit ability in SHEDs isolated from inflamed dental pulp tissues [42]. For the regulatory mechanism, it has been demonstrated that bFGF regulated REX-1 expression in SHEDs via FGFR and Akt pathway [34]. IL-6 is also shown to involve in bFGF induced REX-1 expression as pre-treatment with antibody against IL-6 attenuates REX-1 expression [34].…”
Section: Basic Fibroblast Growth Factor Signalling In Shedsmentioning
confidence: 99%
“…The expression of the surface markers CD44, CD90, CD105, and CD45 were evaluated. The multilineage differentiation protocols were performed according to previous reports [Govitvattana et al, 2013;Nowwarote et al, 2015Nowwarote et al, , 2017. Briefly, cells were cultured in OM (GM supplemented with 50 mg/ml ascorbic acid (Sigma-Aldrich Chemical), 100 nM dexamethasone (Sigma-Aldrich Chemical), and 10 mM b-glycerophosphate (BGP) (Sigma-Aldrich Chemical)) or adipogenic induction medium (AM) (GM supplemented with 0.1 mg/ml insulin, 1 mM dexamethasone, 1 mM IBMX, and 0.2 mM indomethacin).…”
Section: Sheds Characterizationmentioning
confidence: 99%